2016
DOI: 10.1038/srep26276
|View full text |Cite
|
Sign up to set email alerts
|

Glycans affect DNA extraction and induce substantial differences in gut metagenomic studies

Abstract: Exopolysaccharides produced by bacterial species and present in feces are extremely inhibitory to DNA restriction and can cause discrepancies in metagenomic studies. We determined the effects of different DNA extraction methods on the apparent composition of the gut microbiota using Illumina MiSeq deep sequencing technology. DNA was extracted from the stool from an obese female using 10 different methods and the choice of DNA extraction method affected the proportional abundance at the phylum level, species ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 44 publications
0
52
0
Order By: Relevance
“…Several reasons could explain this discrepancy between theoretical profiles and obtained profiles. For example, physical cell-to-cell interactions or the presence of different metabolites may interfere with DNA extraction (16,21). Therefore, based on this synthetic community, no conclusions on the optimal extraction-pipeline combination could be made.…”
Section: Resultsmentioning
confidence: 99%
“…Several reasons could explain this discrepancy between theoretical profiles and obtained profiles. For example, physical cell-to-cell interactions or the presence of different metabolites may interfere with DNA extraction (16,21). Therefore, based on this synthetic community, no conclusions on the optimal extraction-pipeline combination could be made.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that stool contains PCR inhibitors and that the dilution of stool samples may improve PCR sensitivity. [27][28][29][30] Hence, it is possible that the preparation of stool suspensions in our study reduced PCR inhibitors in the sample. This could explain the improved sensitivity of the Chelex method with stool suspension compared with stool directly on the Whatman cards.…”
Section: Discussionmentioning
confidence: 96%
“…DNA was extracted from stool samples after a first mechanical lysis step performed with acid-washed powder (≀106 ”m) glass beads (G4649-500G Sigma-Aldrich, St. Quentin Fallavier, France) and 0.5 mm glass bead cell disruption media (Scientific Industries Inc., Bohemia, NY, USA) using a FastPrep BIO 101 instrument (Qbiogene, Strasbourg, France) at maximum speed (6.5 m/s) for 90s. Then, the stools were further lysed by two methods: (1) the classical lysis and protease step followed by purification on the NucleoSpin tissue kit (Macherey Nagel, Hoerdt, France) (protocol 1) and (2) deglycosylation and purification on the EZ1 Advanced XL device (Qiagen, Courtaboeuf, France) (protocol 5) [31]. Samples were first amplified on each of these two extraction products, then pooled and barcoded.…”
Section: Dna Extraction and 16s Metabarcodingmentioning
confidence: 99%